Corrosion Protection of Al/Mg Compounds by Simultaneous Plasma Electrolytic Oxidation. (2015) - Sieber, M.; Morgenstern, R.; Nickel, D.; Scharf, I.; Alisch, G.; Förster, W.; C. Binotsch; Awiszus, B.; Lampke, T.
Abstract: The application of Al/Mg compound materials for lightweight structures is limited by their corrosion susceptibility. The primary corrosion attack takes place at the Mg component. This may partly be caused by galvanic corrosion and partly by the insufficient formation of a natural passive layer on magnesium. Therefore, oxide coatings were produced on the co-extruded Al/Mg compounds by simultaneous plasma electrolytic oxidation (PEO). A silicate-alkaline and a silicate-phosphate-alkaline electrolyte were used for the coincident production of coatings with a thickness of several 10 microns on both the aluminum and the magnesium component. The inherent flaws of the coating (pores, cavities) allow for the infiltration with an epoxy-based sealant. The electrochemical behavior of the magnesium component covered with the oxide coatings with and without sealing was compared with reference to the unmodified surface. The surface modification (PEO w/wo sealing) significantly decreases the corrosion susceptibility of the Mg component, and thus of the compound.